Jawabanmu

Jawaban paling cerdas!
2014-05-16T01:32:11+07:00
 Cos2x-Cos4x = 0
Cos2x - Cos2(2x) = 0
Cos2x - (2Cos²2x -1) = 0
- 2Cos²2x + Cos2x + 1 = 0
2Cos²x - Cos2x - 1 = 0
(2Cos2x + 1)(Cos2x - 1) = 0
2Cos2x = -1                   atau        Cos2x = 1
Cos2x = -1/2                                       2x = 0 + k.360
       2x = 120' + k.360'                          x = 0 + K.180'
         x = 60' + k.180'                            x = 0' , 180' , 360'
         x = 60' , 240'
HP :{0' , 60' , 180' , 240' , 369'}
1 5 1